The guest house - Morgan-Bentley, Robin (Poisoned Pen Press, 2022)
"An unputdownable thriller with an "oh shit!" beginning for readers of Ruth Ware and Lucy Foley that finds Jamie and Victoria, a married couple expecting their first baby, locked inside the guesthouse they were visiting on vacation just as Victoria feels contractions starting"--